2021
DOI: 10.3390/ijms22094358
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolytic System and Cancer: Diagnostic and Therapeutic Applications

Abstract: Fibrinolysis is a crucial physiological process that helps to maintain a hemostatic balance by counteracting excessive thrombosis. The components of the fibrinolytic system are well established and are associated with a wide array of physiological and pathophysiological processes. The aberrant expression of several components, especially urokinase-type plasminogen activator (uPA), its cognate receptor uPAR, and plasminogen activator inhibitor-1 (PAI-1), has shown a direct correlation with increased tumor growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 135 publications
0
18
0
Order By: Relevance
“…An increasing number of studies have indicated that tumorigenesis is closely associated with abnormalities in the coagulation cascade response in the early stage of tumor. The coagulation system is an integral component of the unique vascular microenvironment for tumor proliferation and progress ( 28 , 29 ). FIB and DD, as important factors in the coagulation cascade and fibrinolysis processes, respectively, have been shown to be involved in the invasive process of a variety of malignancies ( 8 , 19 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have indicated that tumorigenesis is closely associated with abnormalities in the coagulation cascade response in the early stage of tumor. The coagulation system is an integral component of the unique vascular microenvironment for tumor proliferation and progress ( 28 , 29 ). FIB and DD, as important factors in the coagulation cascade and fibrinolysis processes, respectively, have been shown to be involved in the invasive process of a variety of malignancies ( 8 , 19 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that in many carcinoma types, including GOC, the uPAS is a driver of tumour aggressiveness. Not surprisingly, several experimental anti-cancer and imaging approaches targeting various components of the uPAS have been pursued (reviewed in detail by Lin et al [131], Mahmood and Rabbani [15] and Yuan et al [132]). Briefly, anti-uPAS therapeutic approaches include antagonists of uPAR and various uPAR ligand (e.g., uPA, vitronectin, integrins, etc) interactions, small molecule and antibody inhibitors directed against uPA protease activity, PAI-1 inhibitors and uPA-therapeutic drug conjugates [15,131,132].…”
Section: Therapeutics and Diagnostics Directed Towards The Upas Pathwaymentioning
confidence: 99%
“…Not surprisingly, several experimental anti-cancer and imaging approaches targeting various components of the uPAS have been pursued (reviewed in detail by Lin et al [131], Mahmood and Rabbani [15] and Yuan et al [132]). Briefly, anti-uPAS therapeutic approaches include antagonists of uPAR and various uPAR ligand (e.g., uPA, vitronectin, integrins, etc) interactions, small molecule and antibody inhibitors directed against uPA protease activity, PAI-1 inhibitors and uPA-therapeutic drug conjugates [15,131,132]. Our group has previously described the use of PAI-2 conjugated cytotoxins and therapeutic radioisotopes, which were effective in mouse models of human breast and colon cancer [133][134][135][136][137].…”
Section: Therapeutics and Diagnostics Directed Towards The Upas Pathwaymentioning
confidence: 99%
See 2 more Smart Citations